Computed tomography and sonography of hydatid cysts of the liver after surgical management - (:unkn) unknown (My University, 1989)
Twenty-four patients with hydatid cysts of the liver were followed up postoperatively for periods ranging from 6 months to 6 years. In 13 patients in the postoperative period sonography (US) was carried out 48 times and computer tomography (CT) 25 times. Depending on the type of surgical management, the cyst cavity may appear cystic, hypoechoic, or echogenic on postoperative US examination. After omentoplasty, the cyst cavity usually appears to be echogenic. Negative attenuation values due to fat tissue and fluid collection on CT are characteristic signs for omentoplasty. In two cases 2 and 4.5 years after omentoplasty, calcifications were seen within the cyst cavity on CT. Postoperative investigation of the cyst cavity with CT gives more reliable information than with US in evaluating the remaining cyst cavity and differentiating other lesions of the liver.
Keywords: Computed tomography, hydatid cyst; Hydatid cyst, postoperative appearance; Ultrasonography, hydatid cyst